2002
DOI: 10.1074/jbc.m111284200
|View full text |Cite
|
Sign up to set email alerts
|

bcn-1 Element-dependent Activation of the Laminin γ1 Chain Gene by the Cooperative Action of Transcription Factor E3 (TFE3) and Smad Proteins

Abstract: Laminin is a major component of the extracellular matrix. The laminin ␥1 chain is the least variant component of the laminin heterotrimeric assembly. The laminin ␥1 chain gene (LAMC1) expression is induced by several factors, including transforming growth factor-␤ (TGF-␤). LAMC1 promoter contains a highly conserved transcriptional element, bcn-1. We screened cDNA libraries with the yeast one-hybrid system to identify transcriptional factors that are recognized by the bcn-1 motif. Using this strategy we isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…TFE3 and Smad3 can synergistically activate the transcription of PAI-1, Smad7, and laminin ␥1 chain genes (25,26,28,60). The present results demonstrate that other bHLZHIP proteins, including TFEB and Max, can also interact with Smads and influence their transcriptional activities.…”
Section: Effects Of Smad Interactions With Bhlhzip Proteins Onsupporting
confidence: 50%
See 1 more Smart Citation
“…TFE3 and Smad3 can synergistically activate the transcription of PAI-1, Smad7, and laminin ␥1 chain genes (25,26,28,60). The present results demonstrate that other bHLZHIP proteins, including TFEB and Max, can also interact with Smads and influence their transcriptional activities.…”
Section: Effects Of Smad Interactions With Bhlhzip Proteins Onsupporting
confidence: 50%
“…Because TFE3 and Max are distantly related within the bHLHZIP family, it is likely that Smads can interact with many, and perhaps all bHLHZIP family members. It was recently suggested that the laminin promoter can be regulated by Smad interactions with both TFE3 and USF1 (60). Smads have also been shown to interact with Myc, although the interaction interface identified in those studies is outside the conserved bHLHZIP region (29).…”
Section: Effects Of Smad Interactions With Bhlhzip Proteins Onmentioning
confidence: 98%
“…Prior work by LEE et al [32] demonstrated that IL-13 induces lung fibrosis in mice by selective activation of transforming growth factor-b (TGF-b). TGF-b induces expression of laminin a1 chains in rat mesangial cells [33] and laminin c1 chains in mouse distal respiratory epithelial cells [34]. The ability of laminin, via a laminin/nidogen binding site, to form a lattice-type assembly with collagen in the lung matrix may lead to airway wall thickening.…”
Section: Discussionmentioning
confidence: 99%
“…With the use of a yeast one-hybrid approach, the TFE3 transcription factor was cloned from a rat mesangial cell cDNA library, indicating that this basic helix-loop-helix/leucine zipper transcription factor binds to bcn-1. Stimulation of bcn-1 by TGF-␤ to activate the LAMC1 promoter was enhanced by overexpression of Smad3 and was dependent on the Smadbinding element in the LAMC1 promoter (45). In addition, a similar strategy identified binding of the gut-enriched Kruppel-like factor (GKLF) to bcn-1.…”
Section: Cross Talk Between Smad Signaling and Map Kinase Pathwaysmentioning
confidence: 99%
“…Further insight into these events is provided by elegant studies of laminin-␥ 1 gene regulation by Bomsztyk and colleagues (33,45). The LAMC1 promoter contains a highly conserved transcriptional element, termed bcn-1.…”
Section: Cross Talk Between Smad Signaling and Map Kinase Pathwaysmentioning
confidence: 99%